Comprehensive analysis of codon usage patterns of porcine deltacoronavirus and its host adaptability. Issue 5 (19th May 2022) - Peng, Qi; Zhang, Xue; Li, Jizong; He, Wenlong; Fan, Baochao; Ni, Yanxiu; Liu, Maojun; Li, Bin
Abstract: The porcine deltacoronavirus (PDCoV) is a newly discovered pig enteric coronavirus that can infect cells from various species. In Haiti, PDCoV infections in children with acute undifferentiated febrile fever were recently reported. Considering the great potential of inter‐species transmission of PDCoV, we performed a comprehensive analysis of codon usage patterns and host adaptation profiles of 54 representative PDCoV strains with the spike (S) gene. Phylogenetic analysis of the PDCoV S gene indicates that the PDCoV strains can be divided into five genogroups. We found a certain codon usage bias existed in the S gene, in which the synonymous codons are often ended with U or A. Heat map analysis revealed that all the PDCoV strains shared a similar codon usage trend. The PDCoV S gene with a dN/dS ratio lower than 1 reveals a negative selection on the PDCoV S gene. Neutrality analysis showed that natural selection is the dominant force in shaping the codon usage bias of the PDCoV S gene. Unexpectedly, host adaptation analysis reveals a higher adaptation level of PDCoV to Homo sapiens and Gallus gallus than to Sus scrofa . Compared to the USA lineage, the PDCoV strains in the Early China lineage and Thailand lineage were less adapted to their hosts, which indicates that the evolutionary process plays an important role in the adaptation ability of PDCoV. These findings of this study add to our understanding of PDCoV's evolution, adaptability, and inter‐species transmission.